Recitation of Edgar Allan Poe S Poems as a Teaching Tool to Study Features of Connected Speech - Farias-Rojas, G (UNIV LA SALLE, 2016)
This qualitative investigation will consist of designing material for the teaching of English pronunciation to Spanish speakers. This material will be based on both phonetic and phonological theory in the English language and the exercises will aim to provide students with practice in connected speech in the target language by reciting Edgar Allan Poe s poems. According to what was previously stated, this class material will imply a lesson-by-lesson basis whose theoretical background involves the teaching of English as a Foreign Language by teaching students literature presented in the target language. That way, Spanish-speaking students will not only learn English but they will also concentrate on the learning of specific features of English pronunciation.